Beyond the DAG: Visualizing Scheduling Bottlenecks in Task-Based Applications - Fumaco, Alisson dos Passos; Schnorr, Lucas Mello (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2026: Anais da XXVI Escola Regional de Alto Desempenho da Região Sul, 2026)
Diagnosing starvation in task-based runtimes like StarPU typically requires tedious manual inspection of complex Directed Acyclic Graphs (DAGs). We propose a visual methodology that abstracts dependencies to evaluate critical path handling at a glance. Combining an enhanced k-iteration chart with StarVZ’s lackready panel reveals scheduling bottlenecks without granular DAG analysis. We validate this approach by comparing Work Stealing (WS) and Locality Work Stealing (LWS) schedulers executing a tiled QR factorization. Visual evidence confirms WS achieves a statistically significant makespan improvement by sacrificing cache locality to unroll critical tasks, effectively preventing starvation and outperforming LWS.